Effects of cocoa polyphenol-rich extract on the peroxisome proliferator-activated receptor gamma expression in adipose and skeletal muscle tissue of obese diabetic rats - Aminuddin, Farhana (2012)
Theobroma cacao bean is known to have potential anti-obesity and anti-diabetic activities because of its bioactive phytochemicals and their antioxidant capacities. An oral administration of cocoa polyphenols-rich extract (CoPE) (600 mg/kg daily) containing high phenolic (129.877 ± 0.06 mg/ g cocoa extract) and flavonoid (118.92 ± 0.01 mg/g cocoa extract) contents was given to obese-diabetic (Ob-db) induced rats tend to minimize type 2 diabetic condition in 8-weeks of time. As compared to the obese-diabetic (Ob-db) group, increment in body weight and plasma glucose were significantly suppressed for Ob-db with CoPE supplementation. Improvement in lipid profile parameters was also observed with a decrease in total cholesterol (TC), triglyceride (TAG), low density lipoprotein cholesterol (LDL-c), and an elevation in high density lipoprotein cholesterol (HDL-c) levels. However, there was no significant difference in insulin level after 8-weeks of CoPE administration. Oral glucose tolerance test revealed that cocoa supplementation to Ob-db rats significantly reduced plasma glucose at 60 min by 18% compared to unsupplemented Ob-db rats (p < 0.05). The effects of CoPE on the expression of PPAR-γ in adipose tissues and skeletal muscle of Ob-db rats were also evaluated. PPAR-γ known as a key gene regulator for diabetes, and became our interest in improving the status of diabetic condition in Obdb rat’s model supplemented with cocoa bean extract. The regulation of target genes by PPAR-γ activation induces glucose homeostasis, lipid metabolism and adipogenesis. Results from Immunoblotting protein expression showed an overexpression of PPAR-γ in both adipose tissue and skeletal muscle of Ob-db rats supplemented with CoPE. In addition, qRT-PCR results demonstrated that CoPE enhanced PPAR-γ mRNA expression in both adipose tissue and skeletal muscle by 10-fold and 6-fold respectively. However, Ob-db group also showed an increased expression of protein and mRNA PPAR-γ because of the high levels of free-fatty acids presence that forming a natural PPAR-γ ligand without improved any status of diabetic condition. The results suggest that the anti-diabetic activity of CoPE may result from improvement of glucose level, lipid profiles and weight gain. Insulin sensitivity also been improved as assessed by HOMA-IR status. To gain insight, major polyphenol compounds found in CoPE (catechin, epicatechin, caffeine, theobromine and theophylline) might form an active PPAR-γ ligand binding. Thus, the findings may provide a scientific rationale through potential mechanism for the natural antidiabetic action of CoPE through PPAR-γ activation. In addition, PPAR-γ activation by CoPE could play a central role in lipid and glucose homeostasis. Thus, the findings indicated that PPAR-γ is one of a molecular target for CoPE by revealing the mechanism of action in the treatment of type 2 diabetes mellitus, hence suggest that CoPE would be effective in preventing and/or ameliorating the metabolic syndrome.